The Role of Brand Image, Promotions, and Product Quality in Shaping Customer Satisfaction and Loyalty - Stevani Stevani; Silvia Sari Sitompul; Dodi Agusra (International Journal of Information System and Innovation Management (IJISIM), 2023)
This study aims to analyze the effect of brand image, promotion and product quality on the satisfaction and loyalty of supermi consumers in Pekanbaru city either partially or simultaneously. This study uses the analysis of multiple linear regression equations using the SPSS version 21 application, with a total sample of 100 supermi people in the city of Pekanbaru. The results of the first study showed that the brand image and product quality variables had a positive and significant effect on the consumer satisfaction variable, while the promotion variable had a positive but not significant effect on the consumer satisfaction variable. Then in the second test results obtained that the brand image and promotion variables have a positive and significant effect on the consumer loyalty variable, while the product quality variable has no and significant effect on consumer loyalty. Furthermore, in the results of the third test, it is also known that the variable customer satisfaction has a positive and significant impact on the supermi consumer loyalty variable in the city of Pekanbaru.